Chronic non-communicable diseases and COVID-19: EPICOVID-19 Brazil results - Marilia Arndt Mesenburg; Pedro Curi Hallal; Ana Maria Baptista Menezes; Aluísio J D Barros; Bernardo Lessa Horta; Fernando Celso de Barros; Fernando Pires Hartwig; Nadège Jacques; Mariangela Freitas da Silveira (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE Describing the prevalence of chronic diseases and associated socioeconomic and demographic factors, evaluating the patterns of social distancing and the antibodies prevalence against SARS-CoV-2 and COVID-19 symptoms in carriers and non-carriers of chronic diseases. METHODS Data from 77,075 individuals aged 20 to 59 from three steps of the EPICOVID-19 Brazil (a nationwide serological survey conducted between May and June, 2021) were assessed. The presence of antibodies against SARS-CoV-2 was examined by rapid tests. Self-reported prevalence of hypertension, diabetes, asthma, cancer, chronic kidney disease and heart disease were investigated. The prevalence of mask use, adherence to isolation measures and antibodies were evaluated separately amid carriers and non-carriers of chronic diseases. The prevalence of symptoms was analyzed among carriers and non-carriers of chronic diseases with antibodies. RESULTS The prevalence of at least one chronic disease was 43%, higher in the Southeast region, among white and indigenous individuals, women, less schooled and in lower socioeconomic position. The use of masks when leaving home was similar among carriers and non-carriers of chronic diseases (98%). The proportion of participants who reported adherence to isolation measures was higher amid carriers (15.9%) than non-carriers (24.9%) of chronic diseases. The prevalence of antibodies to SARS-CoV-2 was similar amongst carriers and non-carriers (2.4% and 2.3%). The prevalence of cough, dyspnea, palpitations and myalgia was significantly higher among carriers, but the proportion of symptomatic patients was similar between groups. CONCLUSION The prevalence of chronic diseases in Brazil is high and the COVID-19 pandemic affects carriers and non-carriers of chronic diseases similarly. Carriers present more severe forms of COVID-19 and higher prevalence of symptoms. Greater adherence to social distancing measures among chronic patients is disassociated from a lower incidence of COVID-19 in this group.